Bery i bojki slaskie - Ligon, Stanislaw (Katowice : Wydawnictwo PiK, 1994)
A collection of humorous sketches, anecdotes and jokes from the Silesian region.
Keywords: Silesian wit and humor; Anecdotes -- Poland -- Silesia; Folklore -- Poland -- Silesia